Pengaruh Aplikasi Larutan Bawang Putih (Allium sativum) Terhadap Intensitas Serangan Hama Daun Pada Tanaman Pakcoy (Brassica rapa L) - Eza Galang Ramadhani; Helda Orbani Rosa; Muhammad Indar Pramudi (JURNAL PROTEKSI TANAMAN TROPIKA, 2024)
Pakcoy plant (Brassica rapa L.) is a plant that can be planted in low or highlands. However, it is suitable for planting in areas with an altitude of 100-500 m above sea level. Vegetable pesticide solution of garlic (Allium sativum) can be an alternative in suppressing leaf pests on pakchoy plants. The results of the research showed that the application of garlic solution in treatments C (15%) and D (20%) was effective in suppressing leaf pest attacks on pak choy plants by 19.25% and 19.50%.